2017
DOI: 10.1017/s0033291717003221
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral consequences of mild traumatic brain injury in preschoolers

Abstract: Our results show that even in its mildest form, preschool TBI may cause disruption to the immature brain serious enough to result in behavioral changes, which persist for several months post-injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…The complexity and multi‐determinism of social competence (Beauchamp, ) may explain why this domain is vulnerable even to mTBI and why social dysfunction may be present across the range of injury severities. Overall, mTBI may specifically affect the social domain of adaptive functioning because social competence depends on child behavior and family environment which may both be perturbed after mTBI (Gagner et al, ; Ganesalingam et al, ), whereas practical and conceptual adaptive functioning include abilities less likely to be affected after mild brain injury such as motor function (Forsyth & Kirkham, ) and general intelligence (Anderson et al, ; Max et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complexity and multi‐determinism of social competence (Beauchamp, ) may explain why this domain is vulnerable even to mTBI and why social dysfunction may be present across the range of injury severities. Overall, mTBI may specifically affect the social domain of adaptive functioning because social competence depends on child behavior and family environment which may both be perturbed after mTBI (Gagner et al, ; Ganesalingam et al, ), whereas practical and conceptual adaptive functioning include abilities less likely to be affected after mild brain injury such as motor function (Forsyth & Kirkham, ) and general intelligence (Anderson et al, ; Max et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, mTBI may specifically affect the social domain of adaptive functioning because social competence depends on child behavior and family environment which may both be perturbed after mTBI (Gagner et al, 2017;Ganesalingam et al, 2008), whereas practical and conceptual adaptive functioning include abilities less likely to be affected after mild brain injury such as motor function (Forsyth & Kirkham, 2012) and general intelligence (Anderson et al, 2001(Anderson et al, , 2004Max et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was approved by the local institutional ethics review board. Participants were a subgroup recruited as part of a larger prospective longitudinal cohort study aiming to investigate cognitive and social outcomes of early TBI (Bellerose, Bernier, Beaudoin, Gravel, & Beauchamp, ; Dégeilh, Bernier, Gravel, & Beauchamp, ; Gagner, Landry‐Roy, Bernier, Gravel, & Beauchamp, ; Lalonde et al ., ; Landry‐Roy, Bernier, Gravel, & Beauchamp, ). Sixty‐eight children (56% males, M age = 41.9, SD = 11.4 months) with accidental, uncomplicated mTBI aged between 18 and 60 months were recruited over a period of 45 months from December 2011 to August 2015.…”
Section: Methodsmentioning
confidence: 99%
“…14 Eighteen studies reported on psychosocial and behavioral outcomes. 14,16,30,34,37,39,43,[45][46][47][48][49][50][51][52][53][54][55] Generally, social functioning was negatively impacted following early childhood TBI, independent of severity. Acutely, children who experienced a TBI before 6 years of age demonstrated decreased play engagement, including gaze initiation and joint attention.…”
Section: Outcomes Of Early Childhood Tbi and Areas Of Needmentioning
confidence: 97%